EDUCATIONAL VIDEO AS EFFECTIVE COMMUNICATION ON FORMAL AND INFORMAL CAREGIVER TO ELDERLY : A DESCRIPTIVE STUDY - Nurdiansyah, Achmad Fajar Putra; Ahyandi, Syarif Syamsi; Mahesya, Alvian Wahyu; Asmaradianti, Aryunidya; Ilmi, Avida Marisa; Aristya, Meutia Putri; Nurvita, Rani; Nuramalia, Lady Sherly; Narottama, Kadek Rama; Purnami, Nyilo; Lestari, Pudji (Journal of Community Medicine and Public Health Research, 2021)
Presbycusis is a progressive hearing loss which occurs at the age of 65. Communication difficulties caused by these problems are usually not understood or understood by people with normal hearing functions. Therefore, the understanding of these problems must be improved so that there is no gap between people with normal hearing and people with low hearing. The research method used is a quantitative descriptive research design carried out in a number of elderly care foundations. The data we share is in the form of pre-test and post-test questionnaires to elderly caregivers with hearing loss in order to evaluate the caregiver's understanding of the educational video. There was an increase in the understanding of the caregivers about how to communicate effectively based on the comparison of the scores from the pre-test and post-test final scores carried out before and after the education was given. Providing education to caregivers with educational video media provides effective results in increasing caregiver knowledge in this field. The formal caregiver group has better results than the informal caregiver group at 77.7% on the pre-test by formal caregiver and an assessment of 65% on the pre-test by informal caregiver. In the post-test assessment, the formal caregiver got a score of 87.7% and for the informal caregiver it was 90%. There is an increase in the post-test scores of the two caregiver groups after providing education through video media.